Entre fantasmas e mundos imaginários: o fantástico em Virginia Woolf - Faria, Carla Lento [UNIFESP] (2016)
In view of the fantastic literature, this M. A. thesis aims to analyze Virginia Woolf?s short stories "A Haunted House" (1921), "Nurse Lugton's Curtain" (1924), "The Fascination of the Pool" (1929) and "Lappin and Lapinova" (1939). Although Woolf is not fundamentally a writer of the fantastic, some of the author?s short stories showcase narrative procedures and thematic approaches peculiar to this literary mode. The four narratives studied here are developed through traditionally fantastic motifs, like ghosts, space and time suspension, the doppelgänger, inanimate objects coming to life, and so on. Thus, the accurate investigation of these short stories is suitable to demonstrate how Virginia Woolf?s works fall within the tradition of the fantastic literature.